PERLINDUNGAN HUKUM BAGI PRODUK OBAT SIROP PARACETAMOL PADA ANAK (STUDY KASUS GANGGUAN GINJAL AKUT PROGRESIF ATIPIKAL) - Fitri Handayani; Wiwin Muchtar W; Eti Mul Erowati; Elly Kristiani Purwendah (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study aims to determine the legal protection for children who use paracetamol syrup and legal liability for losses experienced by consumers related to cases of using contaminated paracetamol syrup and causing Atypical Acute Progressive Kidney Disorders (AKIRD). The research method used is a normative-empirical approach, with primary, secondary and tertiary data sources in the form of cases of atypical acute progressive kidney disorders, the existing data is analyzed using the deductive method. The results of the analysis state that legal protection that can be obtained by consumers can be in the form of criminal lawsuits, civil lawsuits, administrative lawsuits, assistance from consumer institutions and dispute resolution at BPSK. Legal liability due to the occurrence of Atypical Acute Progressive Kidney Disorders (AKIRD) due to consuming contaminated paracetamol syrup, consumers can request such responsibility to business actors as drug manufacturers in accordance with Article 19 paragraphs 1 and 2 of Law No. 8 of 1999 concerning Consumer Protection, in the form of compensation or compensation. In this case, consumers can also demand accountability from BPOM in accordance with Law No. 36 of 2009 Article 14 concerning health, the claim is based on BPOM negligence, the claim that can be made can use a personal claim or a class action lawsuit. As a form of BPOM responsibility in the form of revoking the distribution permit and carrying out stricter supervision. To prevent similar cases from recurring, stricter supervision is needed on the production and distribution of drugs increasing the standards of good drug manufacturing practices (CPOB) and improving the mechanism for investigation and withdrawal of products from circulation.